Demand and distance: Evidence on cross-border shopping - Marcus Asplund; Richard Friberg; Fredrik Wilander (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
While many studies have documented deviations from the Law of One Price in international settings, evidence is scarce on the extent to which consumers take advantage of price differentials and engage in cross border shopping. We use data from 287 Swedish municipalities to estimate how responsive alcohol sales are to foreign prices, and relate the sensitivity to the location's distance to the border. Typical results suggest that the elasticity with respect to the foreign price is around 0.4 in the border region; moving 200 (400) kilometers inland reduces it to 0.2 (0.1). Given that cross country price differences for alcohol and other products are often caused by taxes, our evidence has implications for the debate on tax competition/harmonization.
Keywords: F15; H20; H77; R12; 330; Law of one price; tax competition; tax harmonization; cross border shopping; European integration; Grenzüberschreitender Verkehr; Konsumentenverhalten; Grenzgebiet; Internationaler Preiszusammenhang; Arbitrage Pricing; Alkoholisches Getränk; Steuerwettbewerb; Schweden